Vegetation inventories from the study: Expansion of deciduous shrubs but not evergreen dwarf shrubs inhibited by reindeer in Scandes mountain range - Vowles, Tage (University of Gothenburg, 2018)
The dataset contains results from vegetation inventories for 1995-2011 from four locations along the Swedish mountain range, for shrub heath and birch forest vegetation types.

Sites surveyed were Fulufjället, Långfjället, Ritsem and Pulsuvuoma.

At each site there are six 25x25m plots, three surrounded by a fence to keep out herbivores, and three representing grazed conditions.

In each of the plots, twenty 1×1m subplots were randomly chosen, and cover for each species in the 1×1m subplots was visually estimated.

This dataset contains the cover data for each species.

Innehåller resultat från vegetationsinventeringar av buskheder och björkskogs vegetationstyper, från fyra platser längs den svenska bergskedjan, 1995-2011.

Undersökta platser: Fulufjället, Långfjället, Ritsem och Pulsuvuoma.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0223
Vegetation inventories from the study: Expansion of deciduous shrubs but not evergreen dwarf shrubs inhibited by reindeer in Scandes mountain range
Keywords: HERBIVORY; VEGETATION COVER; SPECIES/POPULATION INTERACTIONS; FORESTS; SHRUBLAND/SCRUB; ALPINE/TUNDRA; Environmental Sciences; Miljövetenskap; Biota; Biologi och ekologi